1972
DOI: 10.1002/app.1972.070160520
|View full text |Cite
|
Sign up to set email alerts
|

Chain conformations in cellulose I and cellulose II

Abstract: SynopsisThere is strong evidence in the literature that cellulose chains have different conformations, as well as forming different crystalline lattices, in cellulose I and cellulose 11. New data on the birefringence of amine-treated fibers (cellulose 111) support this view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the process of mercerization, the whole fiber was transformed into the swollen state. The assembly and direction of microfibers were broken, and the parallel chain structure of cellulose-I was transformed into the anti-parallel chain structure of cellulose-II (Manjunath and Peacock 1972). Meanwhile, the results above also indicated that the small amount nanocellulose was not able to increase the cellulose-I in the ANF with the cellulose prepared by the acid-alkali method.…”
Section: Xrd Analysismentioning
confidence: 94%
“…In the process of mercerization, the whole fiber was transformed into the swollen state. The assembly and direction of microfibers were broken, and the parallel chain structure of cellulose-I was transformed into the anti-parallel chain structure of cellulose-II (Manjunath and Peacock 1972). Meanwhile, the results above also indicated that the small amount nanocellulose was not able to increase the cellulose-I in the ANF with the cellulose prepared by the acid-alkali method.…”
Section: Xrd Analysismentioning
confidence: 94%